Effects of surface hardening by laser shock peening and shot peening on a nickel-based single-crystal superalloy CMSX-4 - Hakeem, Aabid Husen; Morar, Nicolau I.; Dawson, Karl; Tatlock, Gordon J.; Gibson, Grant J.; Gray, Simon (IOP Publishing, 2024)
Improving the expected life of nickel-based single-crystal superalloy turbine components by surface hardening treatments including laser shock peening (LSP) and mechanical shot peening (MSP) are of particular interest for mitigation of life limiting damage such as environmental assisted cracking in hot section components of gas turbines. In the present study the effects of LSP and MSP on the surface roughness, microhardness and work hardening of a nickel-based single crystal superalloy CMSX-4® have been assessed. Surface roughness was measured using laser profilometry. The degree of work hardening was measured using electron backscattered diffraction with local misorientation analysis. The analysis showed evidence for a work hardening layer in the MSP sample to a depth of approximately 70 μm. Sets of slip bands extending far into the bulk of the sample were observed in the LSP-treated sample, without any evidence of a work hardening layer. Microhardness measurements used to gauge the depth of residual stress showed that LSP produced a much deeper hardness profile than MSP, with compressive residual stress depths of 1000 μm and 200 μm in LSP and MSP respectively. The retention of hardness after a heat treatment of 50 h at 700 °C was more prominent in the LSP sample than in the MSP sample. LSP and MSP have therefore been shown to be at the opposite ends of the spectrum of surface hardening treatments of CMSX-4, with LSP giving milder hardening, but to a greater depth.
Keywords: work hardening; microhardness; laser shock peening; shot peening; nickel single-crystal; 4014 Manufacturing Engineering; 40 Engineering; 4016 Materials engineering; 5104 Condensed matter physics